Midlife dietary patterns and mortality in the population-based study of Swedish twins. Issue 7 (9th April 2013) - Granic, A; Andel, R; Dahl, A K; Gatz, M; Pedersen, N L
Abstract: Background: We examined midlife dietary patterns in relation to (1) sociodemographic and health-related characteristics and (2) survival. Methods: A two-step cluster analysis of a 12-item food questionnaire was used to derive dietary patterns in a cohort of 16 649 members of the Swedish Twin Registry, a prospective, population-based study of twins. The average age at baseline (1967) was 55.5 years; the follow-up for all-cause mortality extended until 2011 (26.8±12.35 years or 345 127 person-years) via death records. Results: Four dietary patterns (classes) distinguishable by demographic and health characteristics emerged: Moderate Intake and Starch Diet (Class 1), Moderate Intake Diet with Low Flour-Based Foods (Class 2), Meat and Starch Diet (Class 3) and Low Meat Intake Diet (Class 4). Membership in Class 3 was associated with 7% increased risk of mortality compared with Class 2 independent of baseline age, cohort, sex and body mass index. These results were mostly explained by sociodemographic and lifestyle factors. When follow-up was restricted to those in the study for 20+ years, both Classes 1 and 3 conferred increased risk of mortality compared with Class 2, independent of covariates. Analyses conducted within twin pairs revealed similar results. Conclusions: Midlife diet over-represented by meat and starch-based foods may increase the risk of mortality, whereas the diet low in starch may be beneficial. These results appear to be independent of factors shared by twins, as well as at least partially a function of social and lifestyle factors, particularly marital status and smoking.